Thoracic heteropagus conjoined twins with associated omphalocele: a case report - Mahamoud Omid Ali Ada; Mansour Issoufou Hama Sidi; Hellé Moustapha; Issoufou Yaro; Oumarou Habou; Habibou Abarchi (Journal of Pediatric Surgery Case Reports)
Introduction: Heteropagus conjoined twins represent an exceptionally rare congenital malformation. A thoracic attachment is even more uncommon. The concurrent presence of omphalocele further complicates management, particularly in resource-limited settings. Case presentation: A 7-day-old female neonate was admitted following a full-term pregnancy and normal vaginal delivery due to a mass in the lower thoracic region, attached to the sternum, with two pelvic limbs and one thoracic limb joined by a pelvis, resembling a parasitic twin. The parasitic twin presented a perineum with female-type external genitalia but no anal orifice. Additionally, a type 2 omphalocele (Aitken classification) with a maximum diameter of 9 cm was observed in the patient's abdomen. Thoraco-abdomino-pelvic computed tomography (CT) imaging revealed osseous segments of limbs within the anterior thoracic mass, alongside herniation of part of the liver through the abdominal wall defect. Echocardiography revealed multiple ventricular septal defects. The diagnosis of a thoracopagus parasitic twin was established. Surgical excision of the parasitic twin was performed at the age of 20 days. A circular incision above the pedunculated base exposed the parasitic pelvis, which contained a rudimentary kidney, dilated ureter, and distended bladder. We did a complete excision included the pelvis, lower limbs, rudimentary upper limb, and osseous components, and finished with a tension-free skin closure. The postoperative recovery was complicated by a minor superficial wound infection, which resolved with antibiotics. We decided to treat the omphalocele conservatively with daily dressing changes to promote skin coverage. We plan to close the omphalocele at the age of 18 months. Conclusion: The management of heteropagus twins requires comprehensive imaging evaluation. In resource-limited settings, patients with a combination of malformations may benefit from a staged treatment strategy to optimize outcomes.